Effect of antibiotic prescribing in primary care on antimicrobial resistance: a literature review 2020 - Alharbi, Bandar A.; Assiri, Abrar A.; Asiri, Khulud A.; Albagli, Dalia A.; Alanazi, Abrar A.; Saleh, Abeer A.; Luheybi, Abdulelah A.; Thabit, Yaser Y.; Alluhaybi, Abdulelah H. (International Journal Of Community Medicine And Public Health, 2020)
Our aim is to review the literature and, where appropriate, investigating subsequent antibiotic resistance in individuals prescribed antibiotics in primary care. Data sources are observational and experimental studies identified through Medline, Embase, and Cochrane searches. Review methods Electronic searches using MeSH terms and text words identified 4373 papers. Results The review included 24 studies, 22 involved patients with symptomatic infection and two involved healthy volunteers, 19 were observational studies (of which two were prospective) and five were randomised trials. The observations concluded that individuals prescribed an antibiotic in primary care for a respiratory or urinary infection develop bacterial resistance to that antibiotic.